The decline of Norwegian kittiwake populations: modelling the role of ocean warming. - Sandvik, Hanno; Reiertsen, Tone K.; Erikstad, Kjell Einar; Anker-Nilssen, Tycho; Barrett, Robert T.; Lorentsen, Svein-Håkon; Systad, Geir Helge; Myksvoll, Mari Skuggedal (Climate Research, 2014)
The black-legged kittiwake Rissa tridactyla is a pelagic seabird whose population has recently declined in most parts of the North Atlantic and which is red-listed in most bordering countries. To investigate a possible cause for this decline, we analysed the population dynamics of 5 kittiwake colonies along the Norwegian coast, ranging from 62° to 71° N, over the last 20 to 35 yr. By quantifying the importance of sea surface temperatures (SST) in relevant areas of the North Atlantic, we tested the importance of climatic conditions throughout the populations’ annual cycles. We found no synchrony among colonies; however, SST affected population dynamics, explaining between 6% and 37% (average 18%) of the variation in annual population growth rate. While dynamics of the southerly colonies were mainly affected by winter conditions in the Grand Banks area, dynamics of the northernmost colonies were dominated by autumn conditions off Svalbard. Negative slopes indicated stronger population decline under warmer ocean conditions. Population dynamics were affected both via adult survival and offspring recruitment, as evidenced by the presence of unlagged effects as well as effects lagged by the age at recruitment. Finally, we performed population viability analyses taking into account the projected warming trends for the future. The median time to extinction of the Norwegian colonies was 52 to 181 yr without considering covariates; 45 to 94 yr when considering the effects of SST but ignoring future warming; and 10 to 48 yr when ocean warming, based on a ‘business as usual’ scenario, was taken into account. Global warming · Non-breeding distribution · Population dynamics · Population viability analysis · Rissa tridactyla · Sea surface temperature